1-(2,3,4,5,6-Pentamethylbenzyl)-2-(pyridin-2-yl)-1H-benzimidazole - Anĝay, Fırat (International Union of Crystallography, 2014)
In the title compound, C(24)H(25)N(3), the benzimidazole ring system is essentially planar, with an r.m.s. deviation of 0.017 Å, and forms dihedral angles of 7.81 (5) and 87.61 (4)° with the pyridine and benzene rings, respectively. An intramolecular C—H⋯N hydrogen bond is observed. In the crystal, molecules are stacked along the a axis by weak C—H⋯π interactions.